CHANGE WE NEED - Bortesi Longhi, Luis (2009)
During his campaign president Obama focalized his message pointing skillful the change as the center of his speech. At the start the message consisted in repeating ¡change, we can believe in it! , and then “change we need” for, finally, like a dart, employing only one word: change. From a theoretical and logical point of view is not easy to assimilate a priori that fact where the most powerful nation in the whole world could be vulnerable because the idea of change, on the contrary, it is supposed that, after all, the USA people means a model to follow as a paradigm of “Developed Society” and therefore a path to pursue, confirming and reinforcing their institutions, the rules, the raison of life, the american dream. Many people still believe in the highest quality of life in America among the entire world. But the electoral experience showed the things in another way demonstrating that the american people is dissatisfied and that the political sense of smell of the candidate Obama target straight in the bull removing the heart and the consciences of the nation. The main purpose in this article is to analyze the causes and circumstances around this phenomenon from a point of view psychological, social and politic.